The Representations of Arab Spring in Feminist Narrative Discourse InThe Arabian Peninsula - Alatawi, Ahmed (Dirasat: Human and Social Sciences, 2021)
The Arab Spring occupied an ample space of the discussion in Arabic culture in the second decade of this century. As Arab woman's literature is an inherent component of Arabic culture, this study aimed to examine the presence of the Arab Spring in a female novelist's writing in the countries of the Arabian Peninsula. This study shows how the female writers deal with the theme of the Arab Spring and how they link it with other themes such as fear, corruption, injustice, freedom, and despair. The novels are: Did you Hear my Speech by Zeinab Hefny, In the Cave of Madness the Story will Begin by Zwaina Al-Kalbaniy, You Will be Fine by Arwa Al-Waqayan, Behind the Sun by Boshra Al-Maqtari, Zeinab's Well by Nadah Shalan, and Ali Muhsin's Market by Nadiyah Al-Kawkabani. This study analyzes these novels from a feminine point of view.